Sand chronicles. Vol. 07 - Ashihara, Hinako (Viz Media, 2010)
"Ann's junior high school reunion is coming up, and she hasn't seen Daigo in two years. How will their reunion go? Then, finally, the story behind Ann's engagement. Who is her fiancé?"--From publisher's web site.